2022
DOI: 10.5829/ije.2022.35.01a.19
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Contaminated Mine Soil and Its Remediation Using Soil Washing Technique - A Case Study on Soil at Kolar Gold Fields

Abstract: Uncontrolled mining and the tailings produced can cause significant environmental impacts such as water, air, and soil pollution. In the present study, a contaminated soil of gold mines located in the Karnataka state of India was studied to know the geotechnical behavior of this soil as a foundation material and to suggest a suitable soil remediation technique to avoid contamination of surrounding water bodies. The in-situ dry unit weight of soil at the selected locations varied from 15.71 to 18.75 kN/m 3 . Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…According to the previous sections, about heavy metal absorption and also according to reported data in literature [1][2][3][4][5][6][7][8][9][10][11][12], it can be concluded that the effect of lead nitrate on shear strength parameters is much higher than that of zinc nitrate. Accordingly, shear strength parameters in lead nitrate contaminated soil were investigated.…”
Section: Shear Strength Parameters Of Contaminated Soilmentioning
confidence: 93%
See 1 more Smart Citation
“…According to the previous sections, about heavy metal absorption and also according to reported data in literature [1][2][3][4][5][6][7][8][9][10][11][12], it can be concluded that the effect of lead nitrate on shear strength parameters is much higher than that of zinc nitrate. Accordingly, shear strength parameters in lead nitrate contaminated soil were investigated.…”
Section: Shear Strength Parameters Of Contaminated Soilmentioning
confidence: 93%
“…Soil type, initial concentration of heavy metals, and their extent in the soil cause changes in soil resistance parameters. As such, studying the behavior of soils contaminated with heavy metals and finding methods to deal with these contaminants is also of great interest in terms of geotechnical issues [4]. One of the most important processes affecting the cause of pollutants in the soil is their absorption by soil particles or adsorbents in the soil composition [5].…”
Section: Introductionmentioning
confidence: 99%
“…A significant volume of tailings produced from processing is generally left as permanent features of the landscape after the mining ceases (15). Coal mining is one of the mines that produces many tailings (ash).…”
Section: 2 Inherent Hydrophobicity Of Coalmentioning
confidence: 99%
“…Cacciuttolo and Cano (25) analyzed the environmental impacts of gold and copper extraction in Chile and Peru, which considered metallurgical processing. Kumar et al (26) analyzed the geotechnical properties and remediation of contaminated soil from gold mines in Karnataka, India. The research sought to characterize the contaminated mine soil geotechnically and identify a soil-washing method to prevent surrounding environmental pollution.…”
Section: Introductionmentioning
confidence: 99%